2016
DOI: 10.1038/nature19326
|View full text |Cite
|
Sign up to set email alerts
|

An endosomal tether undergoes an entropic collapse to bring vesicles together

Abstract: An early step in intracellular transport is the selective recognition of a vesicle by its appropriate target membrane, a process regulated by Rab GTPases via the recruitment of tethering effectors1–4. Membrane tethering confers higher selectivity and efficiency to membrane fusion than the pairing of SNAREs alone5,6,7. Here, we addressed the mechanism whereby a tethered vesicle comes closer towards its target membrane for fusion by reconstituting an endosomal asymmetric tethering machinery consisting of the dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 58 publications
13
145
0
Order By: Relevance
“…, 2008; Cheung et al. , 2015; Murray et al. , 2016), or cell membranes and cytosol to identify components (Cao et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2008; Cheung et al. , 2015; Murray et al. , 2016), or cell membranes and cytosol to identify components (Cao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Four of these subunits, Vps11, Vps16, Vps18, and Vps33, are also components of the HOPS complex found on Rab7-positive vesicles (56). Recent structural studies have shown that these tethering complexes adopt a disordered and highly flexible conformation that coalesces into a tightly ordered structure upon Rab GTPase binding (83)(84)(85). Both of the Rab5-binding subunits that are unique to CORVET, Vps8 and Vps3, were identified in this study as negative regulators of ROMK plasma membrane residence in yeast.…”
Section: Romk Vacuolar Targeting Is Impeded In Yeast Deficient In Escmentioning
confidence: 99%
“…High-resolution OTs achieve extremely high spatiotemporal resolution (~0.3 nm, 20 ms) in a range of force that can reversibly unfold a biomolecule or is generated by molecular motors (Abbondanzieri et al, 2005;Neupane et al, 2016;Moffitt et al, 2006;Zhang et al, 2013;Gao et al, 2012;Cecconi et al, 2005;Bustamante et al, 2004). Recently, OTs have been used to test membrane binding of the vesicle tethering complex EEA1 (Murray et al, 2016). However, to our knowledge, OTs have not been applied to measure both the energy and the detailed kinetics of protein-membrane interactions.…”
Section: Introductionmentioning
confidence: 99%